PENERAPAN SCRUM PADA PENGEMBANGAN SISTEM INFORMASI MANAJEMEN KARYAWAN MELALUI METODE SYSTEMATIC LITERATURE REVIEW - Muhamad Agim Budiman; Dinar Rahayu (STMIK Catur Sakti Kendari, 2026)
This study aims to analyze the application of the Scrum method in the development of an employee management information system. The issues raised focus on identifying the most frequently used Scrum components and the benefits and challenges faced. The research approach was carried out through a literature review of selected journals relevant to the research topic. The analysis results show that the most frequently used components are Sprint Planning and Sprint Review, which emphasize the importance of planning and evaluation in the development process. The implementation of Scrum provides benefits in the form of increased efficiency, transparency, and collaboration, but also presents challenges such as coordination across time, resistance to change, and limited human resources. The success of the implementation is determined by team commitment, understanding of agile principles, and consistent managerial support.